(untitled) (Ágora de Heterodoxias, 2019)
This article describes how culture and citizen participation can be considered the fundamental pillars of Sustainable Development. Culture and development are two terms that have acquired different meanings and have a predominant role in the political agendas of the National States and in the programs of international organizations such as UNESCO, IBD, and the World Bank. Regarding the incorporation of cultural aspects in national strategies, the role of citizen campaigns to lobby to cooperate and promote policies and programs on the role of culture in development stands out. The applied methodology consists of a description and analysis related to the concepts approached about culture and citizen participation as a basis within the establishment of Sustainable Development. It should be underlined that cultural diversity constitutes the main World Heritage Site in all its dimensions from memory, landscape, or creativity, and the search for development could not be disconnected from citizen participation. The government must implement an open attitude, from which the society can manifest itself and the authority has the necessary elements to identify the areas of need and seek a certain way of satisfying it.